Examination of ambiguous stimulus preferences with duration-based measures. - DeLeon, I G (1999)
Items that produced ambiguous results in an approach-based preference assessment were reassessed using a duration-based assessment. The reinforcing effects of three items on free-operant responding were subsequently tested. The results suggested that the duration-based assessment produced slightly more differentiated results and that predictions about reinforcer value, based on this assessment, were accurate.